Scout Practice Digital Teaching Module on the Topic of Scout Knots for Elementary School Students - Putri, Putu Devi Janisa; Sudatha, I Gde Wawan; Jayanta, I Nyoman Laba (International Journal of Elementary Education, 2023)
This research is motivated by problems in Scouting learning that are still confessional so that they are not effectively understood and the use of digital technology that has yet to be maximized. This research aims to develop a quality Digital Teaching Module for Elementary Scout Practices by testing its validity and practicality. This type of research is Research and Development with the ADDIE model. The subjects of this study were two media experts, two material experts, two design experts, two lecturers, and 12 students who had attended scouting lectures. The data collection method used was a questionnaire with an instrument in the form of a rating scale sheet. The data analysis techniques used are descriptive, qualitative, and quantitative. The results showed that: (1) the developed media prototype consists of 3 main parts, namely the opening, core, and closing views; (2) the validity test results show an average score of 93.83% material experts, 96.66% design experts and 95.33% media experts with very good qualifications, (3) the results of the practicality test show an average individual test score of 97.5%, small group test 98.61% and by practitioners of 96.66%. This study concludes that the digital teaching module for elementary scout practices developed is very valid and practical to be developed in learning.